2014
DOI: 10.1103/physrevb.89.184506
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism and superconductivity inSr2VFeAsO3revealed by75As- and

Abstract: We report 75 As-and 51 V-nuclear magnetic resonance (NMR) measurements on the iron-based superconductor Sr 2 VFeAsO 3 with alternating stacks structure. We find that the 75 As nuclear spinspin relaxation rate (1/T 2 ) shows a pronounced peak at T N = 165 K, below which the resonance peak shifts to a higher frequency due to the onset of an internal magnetic field. The 51 V spectrum does not shift, but is broadened below T N . We conclude that the Fe electrons oder antiferromag- shows that superconductivity coex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
2
12
2
Order By: Relevance
“…In contrast to the results reported in Ref. [40], 1/T 2 of 51 V exhibits a second peak around 150 K. The 51 V line barely shifts with temperature, yet it broadens significantly at low T [Fig. 8(a)], in agreement with data reported in Refs.…”
Section: Appendix D: Nuclear Magnetic Resonancesupporting
confidence: 90%
See 2 more Smart Citations
“…In contrast to the results reported in Ref. [40], 1/T 2 of 51 V exhibits a second peak around 150 K. The 51 V line barely shifts with temperature, yet it broadens significantly at low T [Fig. 8(a)], in agreement with data reported in Refs.…”
Section: Appendix D: Nuclear Magnetic Resonancesupporting
confidence: 90%
“…therefore imply V ordering. Reports on 51 V and 75 As nuclear magnetic resonance (NMR) are inconsistent since they either claim Fe magnetism [40,41] or argue in favor of V magnetism [27,38]. NMR measurements on our sample (Appendix D) are in agreement with the literature data to a large extent, but they cannot provide a conclusive answer as to which element carries the ordering moments.…”
Section: μSr and Magnetization Measurementscontrasting
confidence: 50%
See 1 more Smart Citation
“…At optimal doping, the FeAs layer usually prefers C2 magnetism harboring superconductivity while the VO2 layer prefers C4 magnetism [1][2][3]21]. Previous experimental studies of Sr2VO3FeAs [22][23][24][25][26][27][28], however, have reported inconsistent results about magnetic order; recent nuclear magnetic resonance (NMR) measurements on single crystals [29] and neutron diffraction [30] experiments show that there is no long range magnetic order in the V lattice at any temperature while in the Fe lattice a magnetic order with a small moment of ~ 0.05 μ , possibly due to frustration, is developed below 50 K. Indeed, a theoretical GGA calculation has suggested that 4 there can be a number of competing metastable magnetic states composed of different symmetries in V and Fe layers [21]. This is a reasonable theoretical prediction considering the coupling and frustration between V and Fe layers (Supplemental Material Sec.…”
Section: Main Textmentioning
confidence: 99%
“…At optimal doping, the FeAs layer usually prefers C 2 magnetism harboring superconductivity, while the VO 2 layer prefers C 4 magnetism [1][2][3]21]. Previous experimental studies of Sr 2 VO 3 FeAs [22][23][24][25][26][27][28], however, have reported inconsistent results about magnetic order; recent nuclear magnetic resonance (NMR) measurements on single crystals [29] and neutron diffraction [30] experiments show that there is no long-range magnetic order in the V lattice at any temperature, while in the Fe lattice a magnetic order with a small moment of ∼0.05μ B , possibly due to frustration, is developed below 50 K. Indeed, a theoretical generalized gradient approximation (GGA) calculation has suggested that there can be a number of competing metastable magnetic states composed of different symmetries in V and Fe layers [21]. This is a reasonable theoretical prediction considering the coupling and frustration between V and Fe layers (Supplemental Material Sec.…”
mentioning
confidence: 99%